Epigenome-wide association of father's smoking with offspring DNA methylation: a hypothesis-generating study. Issue 4 (6th December 2019) - Mørkve Knudsen, G T; Rezwan, F I; Johannessen, A; Skulstad, S M; Bertelsen, R J; Real, F G; Krauss-Etschmann, S; Patil, V; Jarvis, D; Arshad, S H; Holloway, J W; Svanes, C
Abstract: Epidemiological studies suggest that father's smoking might influence their future children's health, but few studies have addressed whether paternal line effects might be related to altered DNA methylation patterns in the offspring. To investigate a potential association between fathers' smoking exposures and offspring DNA methylation using epigenome-wide association studies. We used data from 195 males and females (11–54 years) participating in two population-based cohorts. DNA methylation was quantified in whole blood using Illumina Infinium MethylationEPIC Beadchip. Comb-p was used to analyse differentially methylated regions (DMRs). Robust multivariate linear models, adjusted for personal/maternal smoking and cell-type proportion, were used to analyse offspring differentially associated probes (DMPs) related to paternal smoking. In sensitivity analyses, we adjusted for socio-economic position and clustering by family. Adjustment for inflation was based on estimation of the empirical null distribution in BACON. Enrichment and pathway analyses were performed on genes annotated to cytosine-phosphate-guanine (CpG) sites using the gometh function in missMethyl. We identified six significant DMRs (Sidak-corrected P values: 0.0006–0.0173), associated with paternal smoking, annotated to genes involved in innate and adaptive immunity, fatty acid synthesis, development and function of neuronal systems and cellular processes. DMP analysis identified 33 CpGs [false discovery rate (FDR)  < 0.05]. Following adjustment for genomic control (λ = 1.462), no DMPs remained epigenome-wide significant (FDR < 0.05). This hypothesis-generating study found that fathers' smoking was associated with differential methylation in their adolescent and adult offspring. Future studies are needed to explore the intriguing hypothesis that fathers' exposures might persistently modify their future offspring's epigenome.